2020
DOI: 10.3329/aajfss.v4i2.53879
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of integrated nutrient management on growth and yield parameters of okra (Abelmoschus esculentus L.)

Abstract: Integrated use of organic and inorganic fertilizers could improve both growth and yield of okra plant. The present study was carried out to evaluate the effect of organic and inorganic fertilizer on growth and yield parameters of okra (Abelmoschus esculentus L.) at experimental area of Noakhali Science and Technology University, Bangladesh during the period of 18th December, 2018 to 19th March, 2019 (Rabi season). In this experiment, “Arka Anamika” variety of okra was used. The experiment was laid out in Rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…The different level of organic and inorganic fertilizers significantly influences the leaf numbers at 50DAS. The maximum number of leaves (14.33cm) was observed with a Full dose of VC +Half dose of NPK (T 8 ) followed by 50%FYM +50%NPK (T 5 ), 50%VC +50%NPK (T 7 ), Full dose of FYM +Half dose of NPK (T 4 ), Recommended dose of NPK (200:180:60) (T 1 ), 125% of NPK(T 2 ), Single dose of vermicompost(15ton/ha) (T 6 ) and FYM @20 ton/ha (T ) which was supported by the findings of Rana et al (2020) and further highlights the essence of organic and inorganic nutrients to influence the yield attributing traits.…”
Section: Effect Of Nutrient Management On Plant Architectural Traitssupporting
confidence: 65%
“…The different level of organic and inorganic fertilizers significantly influences the leaf numbers at 50DAS. The maximum number of leaves (14.33cm) was observed with a Full dose of VC +Half dose of NPK (T 8 ) followed by 50%FYM +50%NPK (T 5 ), 50%VC +50%NPK (T 7 ), Full dose of FYM +Half dose of NPK (T 4 ), Recommended dose of NPK (200:180:60) (T 1 ), 125% of NPK(T 2 ), Single dose of vermicompost(15ton/ha) (T 6 ) and FYM @20 ton/ha (T ) which was supported by the findings of Rana et al (2020) and further highlights the essence of organic and inorganic nutrients to influence the yield attributing traits.…”
Section: Effect Of Nutrient Management On Plant Architectural Traitssupporting
confidence: 65%
“…Amiry et al (2017), and Saurabh et al (2021) also reported that the days to flowering in okra was earliest in the treatment consisting integration of synthetic and organic sources rather than control. It may be due tothe combined effect of chemical fertilizer along with vermicompost and biofertilizer which aided in balanced nutrient supply and improved availability of food material leading to differentiation of bud and initiation of flowers within a short period of time (Amiry et al, 2017;Rana et al, 2020;Mal et al, 2013). Additionally, plant growth-regulating substances (PGRs) present in vermicompost, particularly gibberellin, which play a major role in the regu-lation of flowering could explain the early flower initiation (Rosales and Galinato, 2018;Kist et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…It is one of the cheapest green vegetable of India which is quite popular because of easy cultivation, consistent yield and adaptability to various climatic situations. Okra is commonly grown during summer and rainy seasons for its green, non-fibrous tender fruits (Rana et al, 2020). Fruits are rich in vitamins, calcium, potassium and other mineral matters like iodine which is useful in the treatment of simple goiter (Meena S118 Eco.…”
Section: Introductionmentioning
confidence: 99%